INKONSISTENSI LOGIKA DALAM PERKARA TINDAK PIDANA KORUPSI - Widiada Gunakaya (Komisi Yudisial RI, 2011)
ABSTRACTThe court decision as final phase of enforcement and application of law, as a normative it is properly to reflect material truth, justice values, utility and it has legal certainty will as. In connection with the decision court of BMS No.44/Pid.B/2008/PN.Bms, the accused has been stated proved guilty committed